The Prevalence of Redo-Ureteroneocystostomy and Associated Risk Factors inPediatric Vesicoureteral Reflux Patients Treated with Ureteroneocystostomy - Guney, Dogus; Tiryaki, Tugrul Hüseyin (Urology Journal, 2019)
Purpose: The aim of the study was to examine the prevalence of redo-ureteroneocystostomy (redo-UNC) in pediatric vesicouretheral reflux (VUR) patients following open UNC and factors associated with redo-UNC. Material and methods: Data on 122 patients who underwent open UNC for VUR were analyzed in this retrospective case–control study. The patients were divided into a successful initial UNC group (UNC group, control) and an unsuccessful initial UNC group (redo-UNC group, case). The following variables were analyzed: sex, age, dysfunctional voiding, laterality of VUR (unilateral or bilateral), VUR grade, etiology of VUR (primary or secondary), relative renal function on renal scintigraphy, and surgical technique. The use of the following procedures in the initial UNC was recorded: an endoscopic subureteric injection(ESI) and ureteral tapering. Results: In our clinic, 122 patients (177 ureters), with an average age of 55.7 ± 41.2 months (range, 1–18 years) underwent open UNC for VUR between November 2005 and June 2014. Of these,67 (55%) had unilateral VUR, and 55 (45%) had bilateral VUR. There were 127 (71.8%) cases of grade 4–5 reflux. Postoperatively, hydronephrosis was noted in 19 (15.6%) patents. Ten (8.2%) patients underwent redo-UNC. In eight cases (6.5%), redo-UNC was performed because of ureterovesical (UV) junction obstruction.In the other two cases (1.7%), redo-UNC was due to high-grade reflux. There were no statistically significant differences between the redo-UNC and UNC groups in any of the variables studied. Conclusion: Redo-UNC was required in 10 (8.2%) of cases after UNC. Age, sex, laterality of VUR, VUR grade, existence of primary or secondary VUR, relative renal function on renal scintigraphy, UNC technique, ESI procedure, and ureteral tapering were not risk factors for redo-UNC in our series.